Sound Synthesis, Representation and Narrative Cinema in the Transition to Sound (1926-1935) - Corbella, Maurizio; Windisch, Anna (Cinémas, 2013)
Since the beginnings of western media culture, sound synthesis has played a major role in articulating cultural notions of the fantastic and the uncanny. As a counterpart to sound reproduction, sound synthesis operated in the interstices of the original/copy correspondence and prefigured the construction of a virtual reality through the generation of novel sounds apparently lacking any equivalent with the acoustic world. Experiments on synthetic sound crucially intersected cinema’s transition to synchronous sound in the late 1920s, thus configuring a particularly fertile scenario for the redefinition of narrative paradigms and the establishment of conventions for sound film production. Sound synthesis can thus be viewed as a structuring device of such film genres as horror and science fiction, whose codification depended on the constitution of synchronized sound film. More broadly, sound synthesis challenged the basic implications of realism based on the rendering of speech and the construction of cinematic soundscapes.